Phospholipid Metabolism in the Absence of Net Phospholipid Synthesis in a Glycerol-Requiring Mutant of Bacillus subtilis - Lillich, Thomas T. (1971)
A glycerol-requiring auxotroph of Bacillus subtilis showed no net synthesis of phospholipid when deprived of glycerol. Although there was no net synthesis of phospholipid, we found that: (i) fatty acids and (32)P were slowly incorporated into phospholipid; (ii) in pulse-chase experiments, both (32)P and (14)C in the glycerol portion of the phospholipids were lost from phosphatidlyglycerol (PG) and lysylphosphatidylglycerol and accumulated in cardiolipin (CL); (iii) the proportions of the phospholipids in the membrane changed with a loss of PG and an accumulation of CL. The addition of glycerol to the glycerol-deprived cells resulted in a rapid incorporation of glycerol and restoration to the predeprivation metabolism and PG to CL ratio.